2021
DOI: 10.3389/fphys.2021.627499
|View full text |Cite
|
Sign up to set email alerts
|

The Immunostimulatory Effects of Commercial Feed Additives on Growth Performance, Non-specific Immune Response, Antioxidants Assay, and Intestinal Morphometry of Nile tilapia, Oreochromis niloticus

Abstract: Graphical AbstractThe immunostimulatory effects of commercial feed additives on growth performance, non-specific immune response, antioxidants assay, and intestinal morphometry of Nile tilapia, O. niloticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 66 publications
5
20
0
3
Order By: Relevance
“…The results of the present study revealed that there was no significant difference in SOD and CAT activity between various treatments although the highest levels were reported in probiotic-supplemented groups. In accordance with the results of the current study, Kord et al (2021) reported that the best results for CAT and SOD levels were recorded in Nile tilapia supplemented with Sanolife PRO-F. In a similar sense, supplementation of diet with probiotics in biofloc systems enhanced SOD and CAT in Nile tilapia (Mohammadi et al, 2021) and SOD in red tilapia (Bañuelos-Vargas et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the present study revealed that there was no significant difference in SOD and CAT activity between various treatments although the highest levels were reported in probiotic-supplemented groups. In accordance with the results of the current study, Kord et al (2021) reported that the best results for CAT and SOD levels were recorded in Nile tilapia supplemented with Sanolife PRO-F. In a similar sense, supplementation of diet with probiotics in biofloc systems enhanced SOD and CAT in Nile tilapia (Mohammadi et al, 2021) and SOD in red tilapia (Bañuelos-Vargas et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings presented that fish fed diets enriched with multistrain probiotics displayed higher globulin levels than fish fed no diets enriched with the mono-strain. Similarly, a similar increase in globulin values in the Nile tilapia group fed diets enriched with Sanolife PRO-F (Kord et al, 2021) and Bacilli-based probiotics (Reda & Selim, 2015) was reported. Interestingly, there was a decrease in AST levels in fish groups fed on multi-strain probioticsenriched diets.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is mainly driven by lack of access to high quality food products. Fisheries and aquaculture programs can address and mitigate issues of malnutrition in the world by increasing the access to fish ( 12 , 13 ) due to its nutritional value. Therefore, increasing fish production could increase the access to fish products and improve the nutritional status in children which has the potential to end malnutrition and food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…The Blue crab, Callinectes sapidus, is widely reported in various Mediterranean regions [6,7]. Morphometrics and length-weight relations are often used to evaluate population characteristics [8][9][10] and determine the size of sexual maturity or possible variability among species in the stock assessment of commercially significant species [11,12]. The production of crabs largely depends on the quality of the broodstock, and the male reproductive system information is crucial when collecting the matured males for breeding [13].…”
Section: Introductionmentioning
confidence: 99%